USING NURSERY RHYMES AS ENGLISH TEACHING MEDIA FOR YOUNG LEARNERS - Husni, Na'imatul; Orenzah, Della Teresia (Prodi Pendidikan Bahasa Inggris Universitas Palembang, 2023)
In the learning process, teachers must be able to adapt to the goals, so appropriate supporting factors are needed to achieve these goals, one of which is the use of appropriate teaching media. Songs can be used as an intermediary in learning. Songs have a lot of content in them, for example regarding the content of song lyrics which can be included as learning material. Songs have a high level when it comes to language. The focus of this thesis research is 1) How to plan English learning using nurery rhymes as media? 2) How is English learning carried out using nursery rhymes as media? To identify these problems, this research uses a qualitative descriptive approach. This research uses a case study type. Determining informants using purposive sampling. Data collection techniques use observation, interviews and documentation. The data analysis in this research goes through stages, namely: data collection, data condensation, data presentation and drawing conclusions. Validity of data using triangulation of sources and techniques.